Study of the role of design elements to satisfy the ergonomic needs in car [electronic resource] - Gan, Syn Hong, 1986- (2010)
Project Paper (Sarjana Muda Sains (Rekabentuk Industri)) - Universiti Teknologi Malaysia, 2010